Adhesion formation after surgery for locally advanced colonic cancer in the COLOPEC trial. Issue 4 (5th February 2022) - Zwanenburg, E. S.; Wisselink, D. D.; Klaver, C. E. L.; Brandt, A. R. M.; Bremers, A. J. A.; Burger, J. W. A.; van Grevenstein, W. M. U.; Hemmer, P. H. J.; de Hingh, I. H. J. T.; Kok, N. F. M.; Wiezer, M. J.; Tuynman, J. B.; et al.
Abstract : This study investigated the impact of laparoscopic or open resection of locally advanced colonic cancer on the incidence and severity of adhesions evaluated by laparoscopy at 18 months, primarily intended to evaluate peritoneal recurrence. Open surgery was identified as an independent risk factor for adhesions, but not intraperitoneal chemotherapy.